2004
DOI: 10.1073/pnas.0400851101
|View full text |Cite
|
Sign up to set email alerts
|

Masking of CD22 by cis ligands does not prevent redistribution of CD22 to sites of cell contact

Abstract: CD22, a negative regulator of B cell signaling, is a member of the siglec family that binds to ␣2-6-linked sialic acids on glycoproteins. Previous reports demonstrated that binding of multivalent sialoside probes to CD22 is blocked, or ''masked,'' by endogenous (cis) ligands, unless they are first destroyed by sialidase treatment. These results suggest that cis ligands on B cells make CD22 functionally unavailable for binding to ligands in trans. Through immunofluorescence microscopy, however, we observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
137
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 56 publications
5
137
0
Order By: Relevance
“…The apparent stability of Ly49A/D d cis interaction contrasts with the reversal of CD22/sia cis interaction during cell-cell contact (11). Indeed, soluble, high-avidity CD22 ligands can effectively compete with and replace CD22 cis ligands (30).…”
Section: Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent stability of Ly49A/D d cis interaction contrasts with the reversal of CD22/sia cis interaction during cell-cell contact (11). Indeed, soluble, high-avidity CD22 ligands can effectively compete with and replace CD22 cis ligands (30).…”
Section: Generationmentioning
confidence: 99%
“…In fact, there is a precedent for the latter scenario: CD22 on B cells is largely inaccessible to soluble, multivalent sialoside probes because of CD22 interaction in cis with ␣2-6-linked sialic acids (10). Notwithstanding, CD22 readily redistributes to the site of cell-cell contact in a trans ligand-dependent fashion, implying that trans ligands efficiently compete with cis ligands for CD22 binding on cellular interaction (11). Accordingly, if D d cis and trans ligands compete for Ly49A binding, this could serve to set a threshold for inhibitory signaling in NK cells.…”
mentioning
confidence: 99%
“…Interaction of CD22 with B cell ligands in cis has been suggested to modulate the activity of CD22 as a negative regulator of B cell signaling (23,25,56,57). However, CD22 was initially described as a T cell adhesion protein and has been demonstrated to interact with trans ligands on adjacent cells (23,58,59). Thus, differential regulation of the NeuGc␣2-6Gal sequence may modulate CD22 function through its complex interaction with cis and trans ligands, particularly in B-T cell interactions (e.g., B cell Ag presentation to T cells).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that trans interactions may be important. When cells interact, CD22 redistributes to areas of cell-cell contact (17). This redistribution may be due to the aggregate avidity of many glycoconjugates on a cell interacting with many copies of CD22 on another.…”
mentioning
confidence: 99%
“…Studies examining the carbohydrate specificity of CD22 have revealed its preference for ␣2,6-linked sialylated glycans (16). These glycoconjugates are present on some antigens, yet they also are abundant on the B-cell surface (3,17). Cis interactions between CD22 and proximal glycoconjugates can mask the coreceptor to exogenous (trans) ligands.…”
mentioning
confidence: 99%